2017
DOI: 10.3390/genes8070182
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Origins of Cancer Driver Genes and Implications for Cancer Prognosis

Abstract: The cancer atavistic theory suggests that carcinogenesis is a reverse evolution process. It is thus of great interest to explore the evolutionary origins of cancer driver genes and the relevant mechanisms underlying the carcinogenesis. Moreover, the evolutionary features of cancer driver genes could be helpful in selecting cancer biomarkers from high-throughput data. In this study, through analyzing the cancer endogenous molecular networks, we revealed that the subnetwork originating from eukaryota could contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…Estimation of evolutionary origin can also be complicated by gene loss and depend on the availability of genome sequences. The evolutionary origin of CBL was predicted previously to be the emergence time of opisthokonts [58] , however our results show an eumetazoa origin. On the one hand, the CBL protein family indeed has ancient origin with a predicted ortholog from Dictyostelium, which in fact means a more ancient, Eukaryota origin.…”
Section: Supplementary Materialscontrasting
confidence: 69%
“…Estimation of evolutionary origin can also be complicated by gene loss and depend on the availability of genome sequences. The evolutionary origin of CBL was predicted previously to be the emergence time of opisthokonts [58] , however our results show an eumetazoa origin. On the one hand, the CBL protein family indeed has ancient origin with a predicted ortholog from Dictyostelium, which in fact means a more ancient, Eukaryota origin.…”
Section: Supplementary Materialscontrasting
confidence: 69%
“…Cancer genes, and in particular candidate cancer genes, originated earlier in evolution (Fig. 4b) [37, 58, 59]. Known cancer genes alone do not differ from the rest due to the fact that OGs are significantly younger than TSGs (Fig.…”
Section: Utility and Discussionmentioning
confidence: 99%
“…The results showed that the ubiquitination regulatory gene DZIP3 was significantly correlated with age and changes in immune cell components. In addition, previous studies have shown that genes originating in different stages have different biological functions, which are closely related to human phenotypes (40)(41)(42)(43)(44)(45). Therefore, the evolutionary information of genes often implies important clues to the analysis of human disease mechanisms (40,41,44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have shown that genes originating in different stages have different biological functions, which are closely related to human phenotypes (40)(41)(42)(43)(44)(45). Therefore, the evolutionary information of genes often implies important clues to the analysis of human disease mechanisms (40,41,44). For example, a study had shown that the gene network composed of eumetazoa-originated genes can regulate the hallmarks of cancer (44), reflecting the potential associations of eumetazoaoriginated genes with cancer.…”
Section: Discussionmentioning
confidence: 99%